Connecting Smallholding Farmers: Analysis of Agricultural Market Information Systems (The Case of Wondogenet Wereda, SNNPR, Ethiopia) - Mitiku Kebede Kayamo; Shiferaw Mitiku Tebeka (Turkish Journal of Agriculture: Food Science and Technology)
The study aimed to identify the major challenges that affect the market information system, assess the possible mechanism that would increase their speculative and bargaining capacity power and to explore feasible information system solutions. Data were collected with structured questionnaire from104 farmers of different market using clustered sampling techniques. Descriptive research design and mixed (qualitative and quantitative) research approach vis-à-vis value chain approach is applied and developed an intermediary driven value chain model that links farmers to the market as a way to improve the unidirectional, selectively beneficiary traditional system. Using nine criteria on the multitude of alternative information delivery mechanisms for small holding farmers, Interactive Voice Response based system is found to be of highly effective. Restructuring the market information by bringing the most important wholesalers in to the system, enhancing the functionalities of the market by creating localized price data and creating demand forecasting platform by distinguishing crops that continuously face marketing problems are suggested as short-term action while, increasing economies of scale in production and distribution by consolidating farmers’ cooperatives, encouraging the development of third-party logistics, investing on the physical agro-logistics infrastructure to support long-distance, high-volume agricultural product transportation modes as well as increasing the refrigerated storage capacity at wholesale markets to nurture cold chain technologies are very crucial tasks in the long run.